Diarrhea illness in livestock keeping households in Cambodia: An analysis using a One Health framework - Asakura, Shingo; Khieu, B.; Seng, S.; Pok, S.; Ty, C.; Phiny, C.; Srey, T.; Blacksell, S.D.; Gilbert, Jeffrey; Grace, Delia; Alonso, Silvia (Frontiers Media, 2023)
Background: Most of human diarrheal pathogens are zoonotic, and transmission of the pathogens can occur by contaminated food, water, environment and direct contact with animals especially for livestock keepers. Yet little is known of the relative importance of different risk factors especially in under-studied countries. The objectives of this study were to identify risk factors for diarrhea in livestock keepers in Cambodia and detect diarrhea-causing pathogenic bacteria in both humans and livestock within a One Health approach. Of special interest were the links between diarrhea and food consumption and livestock-keeping.